The Effect of Musk on Pathologic Model of Ischemic Stroke - Gochoo, Radnaa (Caucasus Journal of Health Sciences and Public Health, 2020)
Mongolia is considered to be one of the countries with high rate of cerebrovascular disease prevalence. In traditional Mongolian medicine, musk has been widely utilized in case of cerebral stroke, loss of taste and hypoesthesia. Therefore, we have conducted a research on an animal to study the effects of musk on the Middle Cerebral Artery Occlusion/Reperfusion.